Machinery utilization and production cost of wetland, direct seeding paddy cultivation in Malaysia - Muazu, Aliyu; Yahya, Azmi; Wan Ismail, Wan Ishak; Bejo, Siti Khairunniza (Elsevier (ScienceDirect), 2014)
A mean mechanization index of 0.59 and a total machinery energy of 477.78 MJ/ha were recorded for the direct seeding paddy cultivation in Malaysia. Highest mechanization index and machinery energy were obtained in the harvesting operation (0.99 and 336.81 MJ/ha) while the lowest values were in pesticides operations (0.19 and 3.97 MJ/ha). The benefit-cost ratios for an average farmer with and without government support within the block were respectively 1.37 and 1.68 with a mean yield of 7.63 tons/ha and mean total production cost of RM 6658.18/ha.